Mapping Economic Insights: A Bibliometric Analysis of ASEAN MSME Policy Research (1995–2024) - Isma, Filza; Alexandri , Mohammad Benny; Rahmatunnisa , Mudiyati (Yayasan Riset dan Pengembangan Intelektual, 2025)
Research-based policies are made research position important, hence any research carried out expected can solve MSMEs problems. The research was conducted to map research articles with Scopus indexed ASEAN MSMEs policy topics using bibliometric analysis, therefore it is expected to be a direction for future research. The results show that (1) research on the topic of ASEAN MSMEs policy has increased every year and peak in 2023. (2) Indonesia is a country that influences the topic of ASEAN MSMEs policy by conducting the most publications dan have connections with other countries and Malaysia is the country with the most citations, however Pakistan and Canada are a the highest score of quality of paper. The most cited articles discuss the role of green finance in sustainable entrepreneurship and corporate social responsibility during the COVID-19 pandemic. (3) Keywords associated with MSMEs policy of ASEAN show a shift in focus from industrialization and business strategy in 2007-2019 to topics related to the green economy, sustainability, and the impact of COVID-19 in 2020-2024, therefore this topic can be researched from the perspective of green economy, innovation, and global economy. The main topic of ASEAN MSMEs policy is still relevant today and considering the limited amount of research conducted on this topic, it is anticipated that further research will drive scientific innovation and inform the formulation of policies supporting MSMEs that are more empowered and contribute to encouraging the economy in ASEAN.